Current progress in the authentication of fishery and aquatic products using multi‐element and stable isotope analyses combined with chemometrics. (25th April 2022) - Han, Cui; Li, Li; Dong, Xuan; Gao, Qinfeng; Dong, Shuanglin
Abstract: Fraud occurs frequently in the fishery and aquatic product markets. Therefore, the authentication of fishery and aquatic products has become a crucial issue. Recently, elemental and stable isotope analyses have become popular for aquatic food authentication. In this review, relevant literature was collected to highlight the current progress in the authentication of fishery and aquatic products using multi‐element and stable isotope analyses combined with chemometrics. Both technologies provide valuable insight regarding geographic origin, culture method, and species identification of fishery and aquatic products. Their classification rate varied from 60% to 100% in most studies. The formation of both elemental and stable isotope profiles of fishery and aquatic products is complex and affected by many factors, including diet, biological differences, and culture environment. The classification rate of these methods may be increased by combining multiple technologies, selecting the correct elements and stable isotopes for specific purposes, selecting and verifying proper discrimination methods, and increasing sample sizes. This review provides valuable information to build reliable and stable tracing methods for fishery and aquatic products.